Determinan Pelarangan PraktikShort Selling dalam Lingkup Pasar Modal Syariah dan Realitasnya di Indonesia - R. Adawiyah, Wiwiek; Najmudin, Najmudin (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2011)
Capital  market  is  an  activity  related  to  public offering and trading of securities, public companies relating to the  issuance  of  securities,  institutions  and  professionals associated with the effects. One of the most popular financial instruments  and  commonly  used  in  conventional  capital market,  including  in  Indonesia  Stock  Exchange  (Bursa  Efek Indonesia) is short-selling. In regulation of Bapepam-LK No. V.D.6,  short-selling  is  the  sale  of  securities  in  which  the securities are not owned by the seller when the transaction is executed.  In general,  this  transaction  clearly  violated  syariah guidance,  as  embodied  in  the  Fatwa  of  DSN-MUI  No.  20 Year  2001  and  No.  40  year  2003,  because  of  short-selling synchronized with the bay' ma'dum based on the hadith "You may  not  sell  anything  which  are  not  your  belongings". Therefore, this paper aims at studying the issues surrounding the interpretation and the reality of short-selling instruments. Three  main  results  obtained  were  permissibility  of  shares as the object of the loan contract, the issue of bay 'ma'dum can be  interpreted  as  a collateral  of  delivery  which  can  be controlled  by  the  rules  of  Bapepam-LK, and  thirdly,  the economic benefit from the imposition of a fee in the formof the loan contract is concluded as a forbidden usury.